A feline-focused review of chronic kidney disease-mineral and bone disorders — Part 1: Physiology of calcium handling. (September 2021) - Tang, Pak-Kan; Geddes, Rebecca F.; Jepson, Rosanne E.; Elliott, Jonathan
Highlights: Plasma ionised calcium is subject to rigorous homeostatic control. Potent calciotropic hormone, parathyroid hormone increases circulating calcium. Calcitriol is fundamental in the regulation of intestinal calcium absorption. Fibroblast growth factor 23 and α-Klotho are emerging factors in calcium homeostasis. In adult cats, calcitonin appears to play a minor role in calcium homeostasis. Abstract: Mineral derangements are a common consequence of chronic kidney disease (CKD). Despite the well-established role of phosphorus in the pathophysiology of CKD, the implications of calcium disturbances associated with CKD remain equivocal. Calcium plays an essential role in numerous physiological functions in the body and is a fundamental structural component of bone. An understanding of calcium metabolism is required to understand the potential adverse clinical implications and outcomes secondary to the (mal)adaptation of calcium-regulating hormones in CKD. The first part of this two-part review covers the physiology of calcium homeostasis (kidneys, intestines and bones) and details the intimate relationships between calcium-regulating hormones (parathyroid hormone, calcitriol, fibroblast growth factor 23, α-Klotho and calcitonin) and the role of the calcium-sensing receptor.